Mapping the Trajectory of Tariqa Alawiyya in the 13th-17th Century: The Tension between Expansion and Preservation - Alkadzim, Musa (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2023)
This study delves into the intellectual history of Ṭarīqa ‘Alawiyya, tracing its development from early Alid piety to an Akbarian gnostic tradition, ultimately converging into a revivalist paradigm during the late 16th century. The transformative journey involves a reinterpretation and reformulation of the foundational Akbarian doctrines, strategically tailored to enhance accessibility for both the Ba ‘Alawi community and the broader Muslim society. The focal point of this study is the textual formation of prominent Ba ‘Alawi scholars of the third ṭabaqa, who played a pivotal role in reshaping the Tariqa’s trajectory. While their efforts demonstrably amplified the Tariqa’s influence and reach, they also ignited concerns among some Ba ‘Alawi scholars about the potential dilution of the movement’s unique genealogical configuration. This tension between expansion and preservation gave rise to a parallel restorative movement within the Tariqa, operating concurrently with the reformative movement. This research employs a desk research methodology, drawing upon both textual and contextual data, to examine the intellectual articulations and internal dynamics within the Ṭarīqa ‘Alawiyya. Through the writings of its saintly and scholarly figures, the study investigates how discourse functioned as a tool for negotiating power and reveals the dialogical nature of various canonical texts.